(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A plant-based formulation using an exogenous carrier andor excipient and an alcohol extractfrom a Tecoma species (like Tecoma stans). A composition including a combination of the three acidspresent in the Tecoma species (corosolic acid, oleanolic acid, and ursolic acid) is also provided. Wedetail the use of such formulations in the treatment of skin lesions (including warts, corns, calluses,and umbilical granulomas) and the alleviation of accompanying symptoms. Despite the prevalence ofdermatological conditions including skin illnesses, they are typically disregarded in most communities.This is because, while they rarely pose a direct threat to human life, their aesthetic impact is feltglobally. Eczema, bacterial infections, fungalyeast infections, viral infections, parasitic infections, autoimmunedisorders, and other skin illnesses are all instances of common skin ailments. This studyaimed to manufacture and test the efficacy of a herbal cream comprising an extract of the plant’sflowers preserved in ethanol. Fifteen separate batches, designated FC1 through FC5, were made usingvarying proportions of the active components and tested for their effectiveness. Based on theevaluation parameters, FC5 was shown to be superior to other formulation codes.